(Table 2, Page 106-107) Composition of the HCl-soluble fraction in Barents Sea iron-manganese deposits. - Ingri, J (PANGAEA, 1985)
Ferromanganese concretions from ten stations in the Barents Sea have been analysed for 24 elements. The deposits occur as discoidal and flat concretions and as coatings, in the latter case on lithified or detrital material or as extensive pavements on the Svalbard shelf. The concretions are compositionally similar to Baltic concretions but differ considerably from deep-ocean nodules, particularly in Cu, Ni and Co contents. Statistical analyses reveal distinct correlations between Mn, Na, Ba, Ni and Cu; the Mn-rich coatings showed enrichment of Mo, Zn and possibly Co in a Mn-phase. The iron phase holds high concretions of P and As. Two iron-rich concretions with high contents of P, Ca, Sr, Y, Yb and La were found east and northeast of Spitsbergen Banken, probably indicating upwelling of nutrient-rich, cold polar water along the Svalbard shelf.
Annotated record of the detailed examination of ferromanganese concretions from the Svalbard shelf in the Barents Sea
Keywords: Barents Sea, E of Svalbard; Comment; Deposit type; DEPTH, sediment/rock; Description; Dredge; DRG; Identification; NOAA and MMS Marine Minerals Geochemical Database; NOAA-MMS; Norvarg; NRM_80-BH10; NRM_80-BH11; NRM_80-BH12; NRM_80-BH16; NRM_80-BH19; NRM_80-BH21; NRM_80-BH24; NRM_80-BH26; NRM_80-BH27; NRM_80-BH28; NRM_80-BH5; Position; Quantity of deposit; Sample code/label; Sediment type; Shape; Size; Substrate type; SVALBARDEKSPEDISJONEN-1980; Visual description